1998
DOI: 10.1182/blood.v91.6.2032
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Ligand and Mutation Sites of the Type A Domains of Human von Willebrand Factor and Their Relevance to von Willebrand's Disease

Abstract: Abstractvon Willebrand factor (vWF) is a large multimeric, multidomain glycoprotein found in platelets, endothelial cells and plasma. The A1, A2, and A3 domains in vWF mediate binding to glycoprotein Ib, ristocetin, botrocetin, collagen, sulphatides, and heparin and provide a protease cleavage site. Mutations causing types 2B, 2M, and 2A von Willebrand's disease (vWD) are located in the A1 and A2 domains. Homology modeling was performed to provide a molecular interpretation of vWF function and mutation sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…The Y1605–M1606 bond is inaccessible in native VWF and made sensitive to ADAMTS13 by denaturation and shear force. Structural modelling has suggested that the bond is buried in the core β ‐sheet of the VWF A2 domain (Jenkins et al , 1998; Sutherland et al , 2004). This partially explains the requirement for denaturants or shear force in the hydrolysis of the Y1605–M1606 bond by ADAMTS13.…”
Section: Discussionmentioning
confidence: 99%
“…The Y1605–M1606 bond is inaccessible in native VWF and made sensitive to ADAMTS13 by denaturation and shear force. Structural modelling has suggested that the bond is buried in the core β ‐sheet of the VWF A2 domain (Jenkins et al , 1998; Sutherland et al , 2004). This partially explains the requirement for denaturants or shear force in the hydrolysis of the Y1605–M1606 bond by ADAMTS13.…”
Section: Discussionmentioning
confidence: 99%
“…None of our in vitro experiments supported the hypothesis that the R1583Q substitution might be responsible for the propositus phenotype. The finding that, in the VWFs of many mammals, a glutamine is present at codon 1583 minimizes the role of this amino acid substitution [29]. In contrast, the R202W and C849Y mutations induce drastic amino acid changes, because in the former the small positively charged arginine is replaced by the bulk uncharged tryptophan, and in the latter the loss of a cysteine destroys a disulfide bond [30].…”
Section: Discussionmentioning
confidence: 99%
“…60 Moreover, alignment of the VWF A2 domain sequences across 28 different mammalian species has shown that the consensus sequences for N-linked glycosylation are conserved at both asparagine 1515 and 1574. 61 Previous studies have demonstrated that N-linked glycan structures can directly influence the folding of glycoproteins, by reducing conformational freedom of the local peptide backbone. 62 To further test this hypothesis, we collected plasma from a series of 47 individuals with the rare Bombay phenotype.…”
Section: How Does Abo Blood Group Influence Plasma Vwf Level?mentioning
confidence: 99%